Islamic Perspective on Jamaa'h Prayer During The Covid-19 Pandemic - Mohd Izhar Ariff Mohd Kashim; Kipli Yassin; Mohd Hafiz Safiai; Mohd Helmy bin Mokhtar; Lenny Suryani Safri; Mohd Nasran Mohamad; Nik Salida Suhaila Nik Saleh (Allied Business Academies, 2024)
Indexed by ERA/MyCite